Comics and visual biography: sequential art in social research. Issue 4 (2nd October 2019) - Stephens Griffin, Nathan
Abstract : This article describes the use of comics in a mixed methods biographical research project aimed at understanding the experiences of vegans (i.e. people who eschew animal products such as meat, dairy and eggs). It begins with a discussion of Comics Studies as a growing interdisciplinary field of academic inquiry, and attempts to trace a connection between this and Visual Sociology more broadly. It then provides examples of the way in which comics were used in the project and the rationale underpinning this. Participants were asked to create comics about their lives, which aimed to supplement biographical interviews that had already taken place, eliciting rich 'visual biographical' data that an interview would not produce. Comics were also used as a mode of representation, whereby a 'visual autoethnography' was produced, outlining the author's reflexive autobiographical relationship with veganism, and telling the story of the research. This project presented challenges, specifically around participation, ethics and anonymity, and data analysis. Despite this, the comics produced provided an unusual and valuable insight into the lives and experiences of vegans. To conclude, this article argues that the visual biographical data yielded through the use of the Comics medium represents a valuable tool in visual sociology.